HUBUNGAN PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN KEPATUHAN PEMBATASAN ASUPAN CAIRAN PASIEN HEMODIALISIS - Rini Ernawati; Ismansyah Ismansyah (MNJ (Mahakam Nursing Journal), 2016)
The Chronic Renal Failure (CRF) patients have a regular schedule of hemodialysis therapy generally experience excess extracellular fluid volume because decreased ability kidneys secrete fluid. Patients with chronic renal failure must have a level of knowledge and get a good family support that can be run compliance fluid intake restriction with good and can be increasing the quality of life. The research aims to review the levels of knowledge and know relations social support compliance hearts with Fluid intake restriction Patients with chronic renal failure undergoing hemodialysis therapy in hospitals hemodialysis room. The research method used is a Cross Sectional respondents were determined based on inclusion criteria. Based on the findings of Chi Square test, obtained a knowledge level compliance with hearts fluid intake restrictions namely 0.008 ≤ α (0.05), relationships family support compliance with lead fluid intake restriction p value = 0.004 ≤ α (0.05). there is a knowledge level between relationships and family support compliance with the fluid intake restriction patients with chronic renal failure undergoing yang hemodialysis therapy in hospitals hemodialysis room.